Colorectal cancer in Asians: a demographic and anatomic survey in Malaysian patients undergoing colonoscopy - Goh, Khean Lee; Quek, K-F; Yeo, G.T.S.; Hilmi, I.N.; Lee, C-K; Hasnida, N.; Aznan, M.; Kwan, K-L; Ong, K-T (Blackwell Publishing, 2005)
The demography of colorectal cancer is different from western patients. Tumours were mainly left sided in our patients. However, no differences in anatomic location were found between races, men and women and younger and older age groups. Colorectal cancer presented in an advanced stage in the majority of patients.